Forecasting Analysis: The Riau Islands Local Government Role In Covid-19 Disaster Management - Ramadhani Setiawan; Mahadiansar Mahadiansar (Jurnal Studi Pemerintahan, 2020)
The World Health Organization (WHO) designated COVID-19 as an international pandemic of disaster. The COVID-19 prevention strategy requires the role of international governments, national governments, and also local governments. The Riau Islands is strategic closer to the neighboring countries, which will make the government more aware of the current and future disaster management, which will enable it to face the new normal phase after COVID19. This writing focused on forecasting analysis opinion (Dunn, 2018) identifying future developments. The study used for literature studies reviewed postcode-19 happening in the Riau Islands (content analysis). The researcher suggests two possible scenarios, for the first scene involving a second COVID-19 wave due to a weakness in disaster management. Then the second, new normal scenario will continue with applying policy forecasting. Researchers have also provided an alternative policy forecasting model with approach forecasting analysis: the Potential Future, Plausible Future, and Normative Future concept. This forecasting policy model is expected to be a disaster management guide by local governments in Indonesia.